2019
DOI: 10.2147/ott.s217536
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeting ZEB2 By microRNA-129 In Non-Small Cell Lung Cancer Suppresses Cell Proliferation, Invasion And Migration Via Regulating Wnt/β-Catenin Signaling Pathway And Epithelial–Mesenchymal Transition</p>

Abstract: IntroductionNon-small cell lung cancer (NSCLC) is a common cause of deaths all over the world. Emerging evidence has indicated that microRNA (miR) play key roles in NSCLC progression. We aimed to determine the functions of miR-129 in NSCLC. miR-129 was dramatically downregulated in NSCLC tissue samples and cells. The decreased miR-129 was found to be associated with poorer prognosis and malefic phenotype of NSCLC patients. We demonstrated that miR-129 upregulation could inhibit NSCLC cell growth. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…28 Li et al reported that the overexpression of miR-129 in NSCLC cells could inhibit cell proliferation, invasion and migration by directly regulating ZEB2, and might be a useful biomarker and therapeutic target of NSCLC. 29 To further uncover the functional role of miR-374b-5p in NSCLC progression, we regulated its expression in NSCLC cells and checked its effects on cell biological function. The overexpression of miR-374b-5p was found to inhibit NSCLC cell proliferation, migration and invasion, while the reduction of miR-374b-5p led to the opposite results, indicating that miR-374b-5p might serve as a tumor suppressive miRNA and a potential therapeutic target of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…28 Li et al reported that the overexpression of miR-129 in NSCLC cells could inhibit cell proliferation, invasion and migration by directly regulating ZEB2, and might be a useful biomarker and therapeutic target of NSCLC. 29 To further uncover the functional role of miR-374b-5p in NSCLC progression, we regulated its expression in NSCLC cells and checked its effects on cell biological function. The overexpression of miR-374b-5p was found to inhibit NSCLC cell proliferation, migration and invasion, while the reduction of miR-374b-5p led to the opposite results, indicating that miR-374b-5p might serve as a tumor suppressive miRNA and a potential therapeutic target of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger E-box binding homeobox 2 (ZEB2) is a member of the ZEB family of transcription factors and is known to help mediate EMT (36). In non-small cell lung cancer (NSCLC), miR-129 was found to directly target ZEB2 to inhibit NSCLC cell proliferation (37). miR-129 also regulates the Wnt/β-catenin signaling pathway by decreasing the expression of activated β-catenin, c-Myc and cyclin D1.…”
Section: Lung Cancermentioning
confidence: 99%
“…Given that ZEB2 and miR-6734-3p played opposite regulating role in NSCLC progression [ 23 , 35 ], and there existed regulating relationship between these two genes, we explored whether miR-6374-3p regulated NSCLC development through targeting ZEB2. To validate this hypothesis, we determined the effects of miR-6734-3p/ZEB2 axis on the malignant phenotypes in NSCLC.…”
Section: Resultsmentioning
confidence: 99%